Coaching the female athlete - Miller, Donna Mae (Philadelphia : Lea & Febiger, 1974)
This new International Olympic Committee (IOC) handbook covers the science, medicine and psycho-social aspects of women in sports at all levels of competition. Each chapter focuses on the specific issues that female athletes confront both on and off the field, such as bone health, nutritional recommendations, exercise/competition during menstruation and pregnancy, and much more
Includes bibliography and index
Keywords: Athletic Injuries; Athletes -- psychology; Women's Health